Abiotic stress responses in plants - Zhang, Huiming; Zhu, Jianhua; Gong, Zhizhong; Zhu, Jian-Kang (Nature reviews. Genetics, 2022)
Plants cannot move, so they must endure abiotic stresses such as drought, salinity and extreme temperatures. These stressors greatly limit the distribution of plants, alter their growth and development, and reduce crop productivity. Recent progress in our understanding of the molecular mechanisms underlying the responses of plants to abiotic stresses emphasizes their multilevel nature; multiple processes are involved, including sensing, signalling, transcription, transcript processing, translation and post-translational protein modifications. This improved knowledge can be used to boost crop productivity and agricultural sustainability through genetic, chemical and microbial approaches.